Foamable composition, biodegradable PMI foam and preparation method thereof

By adding an appropriate amount of degradation agent to the foaming composition of the PMI foam, a high-strength and high biodegradable PMI foam is prepared, which solves the problem of difficulty in degrading traditional PMI foam and realizes environmentally friendly waste treatment.

CN119463392APending Publication Date: 2025-02-18HAOBO FUJIAN NEW MATERIAL TECH

Patent Information

Application Number
CN202411679835.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing PMI bubble is difficult to degrade, resulting in difficulty in post-disposal, and economic pressure and environmental pollution problems.

Method used

By adding degrading agents, such as polylactic acid, starch-based polyether polyol and polycaprolactone, to the foaming composition of PMI foam, the proportion of degrading agents is adjusted, and high-strength and high biodegradation rate bioavailable is scientifically prepared. Degrade PMI foam.

Benefits of technology

The high strength and degradability of PMI foam are achieved, and the biodecomposition rate is significantly improved under composting conditions, solving the problem of waste treatment of traditional PMI foam.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005150991960000111
    Figure BDA0005150991960000111
  • Figure BDA0005150991960000131
    Figure BDA0005150991960000131
  • Figure BDA0005150991960000161
    Figure BDA0005150991960000161
Patent Text Reader

Abstract

The invention relates to a foamable composition, biodegradable PMI (polymethacrylimide) foam and a preparation method thereof. The foamable composition comprises comonomers, an initiator, a foaming agent and a cross-linking agent, the comonomers comprise a first comonomer and a second comonomer, the first comonomer is selected from one or two of methacrylonitrile or acrylonitrile, and the second comonomer is selected from methacrylic acid; the composition also comprises a degradation agent, and the degradation agent is selected from one or a combination of more than two of polylactic acid, starch-based polyether polyol and polycaprolactone; the weight ratio of the degradation agent to the comonomer is (30-132): 180. According to the foamable composition disclosed by the invention, the biodegradation rate of the PMI foam is improved and the original high performance of the PMI foam is reserved by scientifically adding the degradation agent and adjusting the formula and adopting an in-situ polymerization technology.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to the technical field of new foaming materials, and in particular to a foamable composition, a biodegradable PMI foam and a preparation method thereof. Background Art

[0002] Polymethacrylimide (PMI) foam is an advanced new material, usually made by foaming methacrylic acid (MAA) and methacrylonitrile (MAN) or by copolymerizing methacrylic acid (MAA) and acrylonitrile (AN). It is easy to process and has excellent strength, stiffness, thermal stability and chemical resistance. It is widely used in aerospace, rail transportation, wind power generation, consumer electronics, medical devices and other fields, and has developed rapidly in recent years.

[0003] However, with the popularization of PMI foam applications, the problem of how to deal with PMI foam after it is discarded has become increasingly prominent and has been troubling the industry. Since PMI foam has excellent high temperature resistance and solvent resistance, it is difficult to degrade in the natural environment. Traditional chemical degradation methods usually need to be carried out in a high temperature and strong alkaline environment, which has the problems of large conditions, high cost and low efficiency; and if the waste is treated by incineration, incineration will increase air pollution.

[0004] In addition, the "white pollution" caused by discarded plastics has always been the focus of environmental protection in the world, and the research and development of degradable plastics is a global trend. For example, patent CN117777602B studied a degradable polypropylene plastic masterbatch, adding a mixture of diethyl dithiocarbamate iron and titanium dioxide to the plastic as a degradation agent, and the photodegradation rate reached 29% in 30 days. Patent CN112063042B studied a degradable polypropylene plastic, using activated carbon-coated cellulose as a degradation agent. Patent US9914824B2 studied a biodegradable polyethylene plastic, using cobalt stearate, iron stearate, cerium stearate, manganese stearate and vanadium stearate as biodegradation agents. The results showed that the plastic garbage bags made would biodegrade within 24-36 months under landfill conditions. Patent CN108264736B studied a degradable PBAT foaming material, adding 1,4-butanediol, hexanediol or ethylene glycol as a degradation agent, which can achieve basically complete degradation in about 2-3 years. US11597235B2 studies a degradable polyurethane foam for tires, by adding dimethyl phosphonate and diethyl phosphonate as degradation agents, so that the polyurethane foam can be degraded at a temperature higher than 120°C.

[0005] Since the widespread use of PMI foam will also generate a large amount of waste, the problem of waste PMI foam disposal needs to be solved urgently. Therefore, the development of environmentally friendly and degradable PMI foam is an important way to implement sustainable development. Summary of the invention

[0006] At present, PMI foam is difficult to degrade, and how to deal with waste PMI foam faces huge economic pressure and environmental problems. Existing studies have disclosed solutions for adding degradation agents to plastics such as polypropylene, polyethylene, PBAT, and polyurethane, which effectively achieve the degradability of plastics such as polypropylene, polyethylene, PBAT, and polyurethane. However, the raw materials, reaction systems, product performance, and application scenarios of these plastics are very different from PMI foams. The types of degradation agents are rich and the properties vary greatly, and not all of them can be used to produce degradable PMI foams. The inventors have not found any research that can effectively achieve the degradation of PMI foam.

[0007] In one aspect, the present disclosure provides a biodegradable PMI foam and a method for preparing the same, which solves the problems of difficult waste treatment, high cost and low efficiency of traditional PMI foam.

[0008] In another aspect, the present disclosure provides a method for converting existing PMI foam into biodegradable PMI foam, which solves the problem of converting existing difficult-to-degrade PMI foam into biodegradable materials.

[0009] In another aspect, the present disclosure provides high strength, high biodegradability PMI foams.

[0010] In another aspect, the present disclosure provides degradation agents that can be used in PMI foams.

[0011] In another aspect, the present disclosure provides a method for increasing the biodegradation rate of PMI foam under composting conditions.

[0012] Specifically, the present disclosure proposes the following technical solutions:

[0013] First, the present disclosure provides a foamable composition, including a comonomer, an initiator, a foaming agent, and a crosslinking agent, wherein the comonomer includes a first comonomer and a second comonomer,

[0014] The first comonomer is selected from one or both of methacrylonitrile and acrylonitrile, and the second comonomer is selected from methacrylic acid;

[0015] The composition further comprises a degradation agent, wherein the degradation agent is selected from one or a combination of two or more of polylactic acid, starch-based polyether polyol, and polycaprolactone;

[0016] The mass ratio of the degradation agent to the comonomer is 30-132:180.

[0017] Optionally, the present disclosure provides a foamable composition according to the foregoing, wherein the comonomer further comprises a third comonomer, and the third comonomer is selected from acrylamide monomers.

[0018] Optionally, the present disclosure provides a foamable composition according to any of the foregoing items, wherein the acrylamide monomer is selected from any one of acrylamide, methacrylamide, N-hydroxymethyl acrylamide, and N,N-dimethyl acrylamide, or a combination of two or more thereof.

[0019] Optionally, the present disclosure provides a foamable composition according to any of the foregoing items, wherein the initiator is selected from any one of azobisisobutyronitrile, azobisisoheptylnitrile, tert-butyl peroxide (2-ethylhexanoate) and dilauroyl peroxide, or a combination of two or more thereof; the foaming agent is selected from any one of formamide, N,N-dimethylformamide, isopropanol, isobutanol, octane and isooctane, or a combination of two or more thereof; and the cross-linking agent is any one of allyl methacrylate and magnesium methacrylate, or both thereof.

[0020] Optionally, the present disclosure provides a foamable composition according to any of the foregoing items, wherein the molecular weight of the polylactic acid is 30,000-150,000, the molecular weight of the polycaprolactone is 10,000-120,000, and the hydroxyl value of the starch-based polyether polyol is 300-600 mgKOH / g.

[0021] Optionally, the present disclosure provides a foamable composition according to any of the preceding items, wherein the degradation agent is selected from polylactic acid.

[0022] Optionally, the present disclosure provides a foamable composition according to any of the foregoing items, wherein the mass ratio of the degradation agent to the comonomer is 50-110:180.

[0023] Optionally, the present disclosure provides a foamable composition according to any of the foregoing items, wherein the mass ratio of the first comonomer to the second comonomer is 0.6-1.5:1.

[0024] Optionally, the present disclosure provides a foamable composition according to any of the foregoing items, wherein, by mass, it comprises 64-120 parts of a first comonomer, 64-120 parts of a second comonomer, 1.2-3 parts of an initiator, 10-18 parts of a blowing agent, 0.8-2.4 parts of a crosslinking agent, 30-132 parts of a degradation agent, and 0-2.4 parts of a third comonomer.

[0025] Optionally, the present disclosure provides a foamable composition according to any of the foregoing items, wherein, by mass, it comprises 72-110 parts of a first comonomer, 72-110 parts of a second comonomer, 1.8-2.75 parts of an initiator, 11.25-16.5 parts of a blowing agent, 0.9-2.2 parts of a crosslinking agent, 40-121 parts of a degradation agent, and 0.9-2.2 parts of a third comonomer.

[0026] Optionally, the present disclosure provides a foamable composition according to any of the foregoing items, wherein, by mass, the first comonomer methacrylonitrile is 72-88 parts, the second comonomer methacrylic acid is 90-110 parts, the third comonomer methacrylamide is 1.8-2.2 parts, the initiator azobisisobutyronitrile is 2-2.75 parts, the blowing agent formamide is 11.25-13.75 parts, the cross-linking agent allyl methacrylate is 1.8-2.2 parts, and the degradation agent polylactic acid is 30-99 parts.

[0027] Optionally, the present disclosure provides a foamable composition according to any of the foregoing items, wherein, by mass, the first comonomer acrylonitrile is 90-110 parts, the second comonomer methacrylic acid is 72-88 parts, the third comonomer acrylamide is 0.9-1.1 parts, the initiator peroxy (2-ethylhexanoic acid) tert-butyl ester is 1.8-2.2 parts, the blowing agent isopropanol is 13.5-16.5 parts, the cross-linking agent magnesium methacrylate is 0.9-1.1 parts, and the degradation agent polylactic acid is 30-99 parts.

[0028] Optionally, the present disclosure provides a foamable composition according to any of the foregoing items, wherein the composition comprises 70-90 parts by mass of a degradation agent.

[0029] Secondly, the present disclosure also provides a biodegradable foam obtained by foaming any of the foamable compositions described above.

[0030] Again, the present disclosure also provides a method for preparing a biodegradable foam, comprising the following steps:

[0031] S1. Prepolymerization: using any of the aforementioned foamable compositions to carry out polymerization reaction to obtain a prepolymer;

[0032] S2, heat treatment before foaming: heat treating the prepolymer to obtain a polymer;

[0033] S3, foaming: foaming the polymer to obtain foam.

[0034] Optionally, the present disclosure provides a preparation method according to any of the foregoing items, wherein, in step S1, the polymerization reaction system contains a degradation agent, a comonomer, an initiator, a foaming agent and a cross-linking agent.

[0035] Optionally, the present disclosure provides a preparation method according to any of the foregoing items, wherein in step S1, the polymerization reaction temperature is 20°C-60°C.

[0036] Optionally, the present disclosure provides a preparation method according to any of the foregoing items, wherein the heat treatment temperature in step S2 is 60°C-120°C.

[0037] Optionally, the present disclosure provides a preparation method according to any of the foregoing items, wherein the foaming temperature in step S3 is 160°C-250°C.

[0038] Optionally, the present disclosure provides a preparation method according to any of the foregoing, further comprising the following steps:

[0039] S4, heat treatment after foaming: heat treating the foam at 135°C-220°C to obtain high temperature resistant foam. The beneficial effects of some embodiments of the present disclosure include:

[0040] The biodegradable PMI foam provided by the present disclosure achieves the high strength and degradability of the PMI foam by scientifically adding a degradation agent and adjusting the proportion of the degradation agent, and maintains sufficient mechanical properties while effectively improving the degradation rate of the PMI foam. DETAILED DESCRIPTION

[0041] The technical solution of the present disclosure will be described clearly and completely below. Obviously, based on the specific implementations of the present disclosure, all other implementations obtained by ordinary technicians in the field without creative work are within the scope of protection of the present disclosure.

[0042] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit the exemplary embodiments according to the present disclosure.

[0043] Methacrylonitrile (MAN) is a colorless liquid organic compound with a chemical formula of C4H5N, a molecular weight of 67.089, and a density of 0.8 g / cm 3 , the molar volume is 82.8 cm 3 / mol. It is slightly soluble in water and chloroform, and miscible with propanol, ether, acetone, octane and toluene.

[0044] Acrylonitrile (AN) is a colorless liquid organic compound with a chemical formula of C3H3N, a molecular weight of 53.063, and a density of 0.806 g / cm 3 , the molar volume is 66.5 cm 3 / mol. Acrylonitrile (AN) is slightly soluble in water, and soluble in ethanol, ether, acetone, benzene and carbon tetrachloride.

[0045] Methacrylic acid (MAA) is a colorless liquid organic compound with a chemical formula of C4H6O2, a molecular weight of 86.089, and a density of 1.015 g / cm 3 , the molar volume is 84.0 cm 3 / mol. Methacrylic acid (MAA) is soluble in hot water and in most organic solvents such as ethanol and ether.

[0046] When methacrylonitrile (MAN) / acrylonitrile (AN) and methacrylic acid (MAA) are copolymerized, a third comonomer is often added. The third comonomer is one or more unsaturated or cyclic monomer molecules that participate in the polymerization reaction. Commonly used ones include acrylamide, methacrylamide, N-hydroxymethyl acrylamide, and N,N-dimethyl acrylamide. Acrylamide is an organic compound in the form of a white crystalline powder with a chemical formula of C3H5NO, a molecular weight of 71.078, and a density of 1.322 g / cm 3 , the molar volume is 73.9 cm 3 / mol, soluble in water, ethanol, ether, acetone, insoluble in benzene and hexane; Methacrylamide is a white crystalline organic compound with a chemical formula of C4H7NO, a molecular weight of 85.104, and a density of 1.115 g / cm 3 , the molar volume is 73.9 cm 3 / mol, it is easily soluble in water, soluble in alcohol and dichloromethane, slightly soluble in ether and chloroform, and insoluble in petroleum ether and carbon tetrachloride; N-hydroxymethyl acrylamide (CAS: 924-42-5) is an organic compound with a colorless or yellow solution, and its chemical formula is C4H7NO2, its molecular weight is 101.1039, and its density is 1.082g / cm 3 N,N-dimethylacrylamide (CAS: 2680-03-7) is a colorless liquid with the chemical formula C5H9NO. It has good solubility and reactivity and is mostly used in the synthesis and modification of polymers.

[0047] An initiator is a compound with a weak bond, which is easily decomposed into active species and decomposed into free radicals when heated. It is used to initiate free radical polymerization and copolymerization reactions of olefin and diene monomers, and can also be used for cross-linking and curing of unsaturated polyesters and cross-linking reactions of polymers; commonly used initiators include azobisisobutyronitrile, azobisisoheptanenitrile, tert-butyl peroxide (2-ethylhexanoate), and dilauroyl peroxide. Azobisisobutyronitrile (CAS: 78-67-1) is a white needle-shaped crystal, and a white powdery crystal when the purity is low; it is insoluble in water, but soluble in organic solvents such as methanol, ethanol, acetone, ether, petroleum ether, toluene, and aniline; it is used as an initiator for the polymerization of monomers such as vinyl chloride, vinyl acetate, and acrylonitrile. Azobisisoheptanenitrile (CAS: 4419-11-8) is a colorless or white rhombus-shaped flaky crystal; it is insoluble in water, but soluble in organic solvents such as alcohol, ether, and dimethylformamide; it can be used as a polymerization initiator for polymer compounds such as polyvinyl chloride, polyvinyl alcohol, and polymethyl methacrylate. Tert-butyl peroxide (2-ethylhexanoate) (CAS: 3006-82-4), also known as TBPO, is an organic peroxide initiator. It is a colorless or light yellow transparent liquid. It is used as a polymerization initiator for all vinyl monomers such as vinyl acetate, vinyl chloride, methacrylic acid, styrene, and ethylene. It can also be used as a thermal molding and curing catalyst for unsaturated polyester resins. Dilauroyl peroxide (CAS: 105-74-8), also known as initiator B, is a white powder that is easily soluble in organic solvents such as acetone and chloroform and oils, but insoluble in water. It is mainly used as a free radical polymerization initiator and is often used in combination with initiator A (di-tert-butyl peroxide).

[0048] Foaming agents are compounds that release gases such as carbon dioxide and nitrogen after heating and decomposition, and form pores in the polymer composition. Foaming agents are used to reduce the surface tension of the liquid, and arrange the double electron layer on the surface of the liquid film to surround the air, forming bubbles, and then the single bubbles form foam. Commonly used foaming agents include formamide, N, N-dimethylformamide, isopropanol, isobutanol, octane, and isooctane. Formamide (CAS: 75-12-7) is a transparent oily liquid that is miscible with water and ethanol, and slightly soluble in benzene, chloroform and ether. N, N-dimethylformamide (CAS: 68-12-2), with the chemical formula C3H7NO, is a colorless and transparent liquid. It can be mixed with water and most organic solvents at will, and has good solubility for a variety of organic and inorganic compounds. Isopropyl alcohol (CAS: 67-63-0) is a colorless, flammable liquid with a strong odor at room temperature and pressure. It is miscible with water, alcohol, ether and chloroform, and its boiling point is 82°C. Isobutanol (CAS: 78-83-1) is a colorless transparent liquid, miscible with ethanol and ether, soluble in about 20 parts of water, and its boiling point is 108°C. Octane (CAS: 111-65-9) is a colorless transparent liquid with a boiling point of 125.67°C. Isooctane (CAS: 540-84-1) is a colorless, transparent liquid, insoluble in water, soluble in ether, easily soluble in alcohol, acetone, benzene, chloroform, etc., with a boiling point of 98-99°C.

[0049] Crosslinking agents are insoluble substances with three-dimensional structures that generate diradicals after exposure and react with polyolefin resins to form bridge bonds between polymer molecular chains. They are soluble in aromatic hydrocarbons, halogenated hydrocarbons, cycloalkanes, acetone, various alcohols, etc., slightly soluble in alkanes, and insoluble in water. Commonly used crosslinking agents include allyl methacrylate, magnesium methacrylate, etc. Allyl methacrylate (CAS: 96-05-9) is a slightly yellow liquid that is easily soluble in most organic solvents and almost insoluble in water. It is an important crosslinking agent. Magnesium methacrylate (CAS: 7095-16-1) is a white crystalline solid. It is soluble in water and some organic solvents, such as ethanol and ether. It is often used as a rubber additive to improve the crosslinking properties of rubber.

[0050] Degradation agents are a new type of functional additives that meet environmental protection requirements. They are added to plastics to make them easy to degrade. They are mainly used to solve the white pollution problem that has long plagued people. There are two ways to add degradation agents as additives to the PMI foam reaction system. One is to add them in the polymerization stage by in-situ polymerization, and the other is to use a staged mixing method to mix them in after the polymerization is completed and before foaming.

[0051] In the present disclosure, in-situ polymerization refers to a process in which both the degradation agent and the comonomer are added to a polymerization reaction system for polymerization reaction. In-situ polymerization allows the degradation agent to participate in the polymerization reaction and be evenly dispersed in the prepolymer.

[0052] The staged mixing in the present disclosure refers to the process in which after the copolymerization of the comonomer is completed, the polymer is crushed, the degradation agent and the resin are added, and after being stirred evenly, a high-temperature foaming reaction is further performed, so that the degradation agent is bonded into one body through the resin and the PMI foam during the foaming process.

[0053] In order to promote the degradation of PMI foam in the natural environment, the inventors added a degradation agent before foaming, so that the PMI foam after foaming is easy to degrade, and is used to solve the white pollution problem that has long troubled people.

[0054] In order to match the production system and processing application scenarios of PMI foam, and to find a suitable degradation agent, the inventors studied iron diethyldithiocarbamate, titanium dioxide, iron stearate, ethylene glycol, 1,4-butanediol, hexanediol, starch, cellulose acetate, chitosan, polyglycolic acid (PGA), polydioxanone (PPDD), polycaprolactone (PCL), polyhydroxybutyrate (PHB), poly (3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV), polylactic acid (PLA), butylene terephthalate (PBAT), polybutylene succinate (PBS), polyvinyl alcohol (PVA) and other degradation agents. After evaluating the polymerization reaction and degradation effect of PMI foam after adding degradation agents, it was found that starch-based polyether polyols, polylactic acid (PLA), and polycaprolactone (PCL) can be used in PMI foam as degradation agents. Starch-based polyether polyols are polyols prepared with starch as raw material and glycerol-polyethylene glycol as liquefier. Polylactic acid (CAS: 26100-51-6) is a polymer formed by the polymerization reaction of lactic acid molecules. It is difficult to dissolve in general organic solvents, but it can be dissolved faster in the hot state or after mixing with some ester or ether solvents; Polylactic acid is a biodegradable polymer that can be degraded into harmless products by the action of microorganisms in the natural environment and is environmentally friendly. Polycaprolactone (CAS: 24980-41-4), also known as poly-ε-caprolactone, is a high molecular organic polymer formed by ring-opening polymerization of ε-caprolactone monomers under the catalysis of metal anion complex catalysts; Polycaprolactone is a biodegradable polymer that is non-toxic, biodegradable in soil, has excellent miscibility, is mechanically compatible with many polymers, and has good adhesion to many substrates.

[0055] Some embodiments of the present disclosure provide a foaming composition, the components of which include a comonomer, an initiator, a foaming agent, a crosslinking agent, and a degradation agent. At least two comonomers are required to prepare PMI foam, the first comonomer is selected from one or both of methacrylonitrile or acrylonitrile, and the second comonomer is selected from methacrylic acid. The degradation agent is selected from one or a combination of two or more of polylactic acid, starch-based polyether polyol, and polycaprolactone. In some embodiments of the present disclosure, the mass ratio of the degradation agent to the comonomer is, for example, 30-132:180; for example, 30:180, 35:180, 40:180, 45:180, 50:180, 55:180, 60:180, 65:180, 70:180, 75:180, 80:180, 85:180, 90:180, 95:180, 100:180, 105:180, 110:180, 115:180, 120:180, 125:180, 130:180, 132:180.

[0056] In some embodiments of the present disclosure, the degradation agent is selected from starch-based polyether polyols. Optionally, the hydroxyl value of the starch-based polyether polyol is 300-600 mgKOH / g, such as 300 mgKOH / g, 350 mgKOH / g, 400 mgKOH / g, 450 mgKOH / g, 500 mgKOH / g, 550 mgKOH / g, 600 mgKOH / g; the hydroxyl value of the optional starch-based polyether polyol is 400-500 mgKOH / g, such as 400 mgKOH / g, 410 mgKOH / g, 420 mgKOH / g, 420 mgKOH / g, 440 mgKOH / g, 450 mgKOH / g, 460 mgKOH / g, 470 mgKOH / g, 480 mgKOH / g, 490 mgKOH / g, 500 mgKOH / g.

[0057] In some embodiments of the present disclosure, the degradation agent is selected from polycaprolactone. Optionally, in some embodiments of the present disclosure, the molecular weight of polycaprolactone is 10,000-120,000, for example, 10,000, 20,000, 30,000, 40,000, 50,000, 60,000, 70,000, 80,000, 90,000, 100,000, 110,000, 120,000, optionally 20,000-110,000, 30,000-110,000, 40,000-100,000, 50,000-100,000, 60,000-90,000.

[0058] In some embodiments of the present disclosure, the degradation agent is selected from polylactic acid, so that the foam prepared by the foaming composition obtains a good biodegradation rate and mechanical properties. Optionally, in some embodiments of the present disclosure, the molecular weight of the polylactic acid is 30,000-150,000, such as 30,000, 40,000, 50,000, 60,000, 70,000, 80,000, 90,000, 100,000, 110,000, 120,000, 130,000, 140,000, 150,000, such as 50,000-140,000, 70,000-120,000, 80,000-110,000.

[0059] The foamable composition provided by some embodiments of the present disclosure comprises, by mass, 64-120 parts of the first comonomer, 64-120 parts of the second comonomer, 1.2-3 parts of the initiator, 10-18 parts of the foaming agent, 0.8-2.4 parts of the crosslinking agent, 30-132 parts of the degradation agent, and 0-2.4 parts of the third comonomer. Optionally, the degradation agent in the foamable composition provided by some embodiments of the present disclosure is, by mass, for example, 30 parts, 35 parts, 40 parts, 45 parts, 50 parts, 55 parts, 60 parts, 65 parts, 70 parts, 75 parts, 80 parts, 85 parts, 90 parts, 95 parts, 99 parts; for example, 40-95 parts, for example, 50-110 parts; further, for example, 50-100 parts; further, for example, 50-90 parts; further, for example, 60-90 parts; further, for example, 70-90 parts; further, for example, 75-90 parts; further, for example, 75-85 parts.

[0060] The foamable composition provided in some embodiments of the present disclosure comprises, by mass, 72-110 parts of a first comonomer, 72-110 parts of a second comonomer, 1.8-2.75 parts of an initiator, 11.25-16.5 parts of a foaming agent, 0.9-2.2 parts of a cross-linking agent, 40-121 parts of a degradation agent, and 0.9-2.2 parts of a third comonomer. Optionally, the degradation agent in the foamable composition provided in some embodiments of the present disclosure is, by mass, for example, 30 parts, 35 parts, 40 parts, 45 parts, 50 parts, 55 parts, 60 parts, 65 parts, 70 parts, 75 parts, 80 parts, 85 parts, 90 parts, 95 parts, 99 parts; for example, 40-95 parts, for example, 50-110 parts; for example, 50-100 parts; further for example, 50-90 parts; further for example, 60-90 parts; further for example, 70-90 parts; further for example, 75-90 parts; further for example, 75-85 parts.

[0061] The foamable composition provided in some embodiments of the present disclosure comprises, by mass, 80-100 parts of the first comonomer, 80-100 parts of the second comonomer, 2-2.5 parts of the initiator, 12.5-15 parts of the foaming agent, 1-2 parts of the crosslinking agent, 30-110 parts of the degradation agent, and 1-2 parts of the third comonomer. Optionally, the degradation agent in the foamable composition provided in some embodiments of the present disclosure is, by mass, for example, 30 parts, 35 parts, 40 parts, 45 parts, 50 parts, 55 parts, 60 parts, 65 parts, 70 parts, 75 parts, 80 parts, 85 parts, 90 parts, 95 parts, 99 parts; for example, 40-95 parts, for example, 50-100 parts; further, for example, 50-90 parts; further, for example, 60-90 parts; further, for example, 70-90 parts; further, for example, 75-90 parts; further, for example, 75-85 parts.

[0062] The foamable composition provided in some embodiments of the present disclosure comprises, by mass, 72-88 parts of methacrylonitrile as a first comonomer, 90-110 parts of methacrylic acid as a second comonomer, 1.8-2.2 parts of methacrylamide as a third comonomer, 2-2.75 parts of azobisisobutyronitrile as an initiator, 11.25-13.75 parts of formamide as a foaming agent, 1.8-2.2 parts of allyl methacrylate as a crosslinking agent, and 30-99 parts of polylactic acid as a degradation agent. Optionally, the degradation agent in the foamable composition provided in some embodiments of the present disclosure is, by mass, for example, 30 parts, 35 parts, 40 parts, 45 parts, 50 parts, 55 parts, 60 parts, 65 parts, 70 parts, 75 parts, 80 parts, 85 parts, 90 parts, 95 parts, 99 parts; for example, 40-95 parts, further for example, 50-90 parts; further for example, 60-90 parts; further for example, 70-90 parts; further for example, 75-90 parts; further for example, 75-85 parts.

[0063] Some embodiments of the present disclosure provide a foamable composition, whose components, by mass, include 90-110 parts of acrylonitrile as a first comonomer, 72-88 parts of methacrylic acid as a second comonomer, 0.9-1.1 parts of acrylamide as a third comonomer, 1.8-2.2 parts of tert-butyl peroxide (2-ethylhexanoate) as an initiator, 13.5-16.5 parts of isopropyl alcohol as a foaming agent, 0.9-1.1 parts of magnesium methacrylate as a crosslinking agent, and 30-99 parts of polylactic acid as a degradation agent. Optionally, the degradation agent in the foamable composition provided in some embodiments of the present disclosure is, by mass, for example, 30 parts, 35 parts, 40 parts, 45 parts, 50 parts, 55 parts, 60 parts, 65 parts, 70 parts, 75 parts, 80 parts, 85 parts, 90 parts, 95 parts, 99 parts; for example, 40-95 parts, 50-90 parts; further for example, 60-90 parts; further for example, 70-90 parts; further for example, 75-90 parts; further for example, 75-85 parts.

[0064] The foamable composition provided by some embodiments of the present disclosure comprises, by mass, 80 parts of methacrylonitrile as the first comonomer, 100 parts of methacrylic acid as the second comonomer, 2 parts of methacrylamide as the third comonomer, 2.5 parts of azobisisobutyronitrile as the initiator, 12.5 parts of formamide as the foaming agent, 2 parts of allyl methacrylate as the crosslinking agent, and 30-90 parts of polylactic acid as the degrading agent. Optionally, the degrading agent in the foamable composition provided by some embodiments of the present disclosure is, by mass, for example, 30 parts, 35 parts, 40 parts, 45 parts, 50 parts, 55 parts, 60 parts, 65 parts, 70 parts, 75 parts, 80 parts, 85 parts, 90 parts, 95 parts, 99 parts; for example, 40-95 parts, for example, 50-90 parts; further, for example, 60-90 parts; further, for example, 70-90 parts; further, for example, 75-90 parts; further, for example, 75-85 parts.

[0065] The foamable composition provided by some embodiments of the present disclosure comprises, by mass, 100 parts of acrylonitrile as the first comonomer, 80 parts of methacrylic acid as the second comonomer, 2 parts of methacrylamide as the third comonomer, 2 parts of tert-butyl peroxide (2-ethylhexanoate) as the initiator, 15 parts of isopropanol as the foaming agent, 1 part of magnesium methacrylate as the crosslinking agent, and 30-90 parts of polylactic acid as the degradation agent. Optionally, the degradation agent in the foamable composition provided by some embodiments of the present disclosure is, by mass, for example, 30 parts, 35 parts, 40 parts, 45 parts, 50 parts, 55 parts, 60 parts, 65 parts, 70 parts, 75 parts, 80 parts, 85 parts, 90 parts, 95 parts, 99 parts; for example, 40-95 parts, for example, 50-90 parts; further, for example, 60-90 parts; further, for example, 70-90 parts; further, for example, 75-90 parts; further, for example, 75-85 parts.

[0066] Some embodiments of the present disclosure provide a biodegradable foam obtained by foaming the foamable composition according to some embodiments of the present disclosure.

[0067] Some embodiments of the present disclosure provide a method for preparing a biodegradable foam, comprising the following steps:

[0068] S1. Prepolymerization: A prepolymer is obtained by polymerizing the foamable composition of some embodiments of the present disclosure; optionally, the polymerization reaction system contains a degradation agent, a comonomer, an initiator, a foaming agent and a crosslinking agent, so that the degradation agent and the comonomer are polymerized in situ; optionally, the polymerization reaction temperature is 20° C.-60° C., and can further be 35-50° C.;

[0069] S2, heat treatment before foaming: heat treating the prepolymer to obtain a polymer; optionally, the heat treatment temperature is 60°C-120°C, and can further be 100-120°C;

[0070] S3, foaming: foaming the polymer to obtain foam; optionally, the foaming temperature is 160°C-250°C, optionally 180-250°C, and further the foaming temperature is 200-220°C.

[0071] The preparation method provided in some embodiments of the present disclosure further comprises the following steps:

[0072] S4, heat treatment after foaming: heat treating the foam at 135°C-220°C to obtain high temperature resistant foam; optionally baking the foam at 150°C-220°C; optionally baking the foam at 180°C-220°C to obtain high temperature resistant foam.

[0073] Some embodiments of the present disclosure also provide a method for preparing a biodegradable PMI foam, the preparation steps of which are as follows:

[0074] S0. Ingredients: Add 1-100 parts of methacrylonitrile or acrylonitrile, 1-100 parts of methacrylic acid, 0-10 parts of the third comonomer, 0.1-10 parts of initiator, 0.1-20 parts of foaming agent, 0.1-10 parts of crosslinking agent, and 50-90 parts of degradation agent into the reactor according to the weight parts, stir evenly, mix thoroughly at room temperature, and then pour into the mold.

[0075] S1. Polymerization: placing the mold in a constant temperature water bath at 20°C-60°C for 5-15 days to allow the degradation agent to polymerize in situ with the MAA / MAN / AN comonomer to obtain a polymethacrylimide (PMI) prepolymer containing a degradation agent block;

[0076] S2, pretreatment: putting the PMI prepolymerized board into a circulating air oven at 60°C-120°C for post-treatment for 6 hours-20 hours to obtain a PMI polymerized board;

[0077] S3, foaming: foaming the PMI polymer sheet at 160°C-250°C; optionally 180-250°C; further the foaming temperature is 200-220°C; optionally, foaming at the aforementioned foaming temperature for 4 hours to 8 hours to obtain PMI foam;

[0078] S4. Heat treatment: PMI foam is baked at 135℃~220℃, optionally at 150℃-220℃; optionally at 180℃-220℃

[0079] Baking; optionally, after baking at the aforementioned baking temperature for 20 hours to 48 hours, a high temperature resistant PMI foam can be obtained.

[0080] The biodegradable foams according to some embodiments of the present disclosure are described below by means of specific examples. The raw materials used in the following examples are all conventional commercially available products.

[0081] in,

[0082] Methacrylonitrile: Purity ≥ 99.5%

[0083] Methacrylic acid: purity ≥99%

[0084] Methacrylamide: Purity ≥98%

[0085] Acrylamide: Purity ≥98%

[0086] Azobisisobutyronitrile: Purity ≥ 99%

[0087] Tert-butyl peroxy (2-ethylhexanoate): Purity: ≥97%

[0088] Formamide: Purity ≥ 99.5%

[0089] Isopropyl alcohol: purity ≥99%

[0090] Propyl methacrylate: purity ≥95%

[0091] Magnesium methacrylate: purity ≥98%

[0092] Polylactic acid: molecular weight: 70,000 to 120,000

[0093] Polycaprolactone: molecular weight: 50,000 to 100,000

[0094] Starch-based polyether polyol: The hydroxyl value of the polyol is 400-500 mgKOH / g.

[0095] Example 1

[0096] The foamable composition comprises 80 parts of methacrylonitrile as a first comonomer, 100 parts of methacrylic acid as a second comonomer, 2 parts of methacrylamide as a third comonomer, 2.5 parts of azobisisobutyronitrile as an initiator, 12.5 parts of formamide as a foaming agent, and 2 parts of allyl methacrylate as a crosslinking agent.

[0097] S0. Ingredients: Add 80 parts of methacrylonitrile, 100 parts of methacrylic acid, 2 parts of methacrylamide, 2.5 parts of azobisisobutyronitrile, 12.5 parts of formamide, and 2 parts of allyl methacrylate into a reaction kettle according to the weight parts, stir evenly, mix thoroughly at room temperature, and then pour into a mold;

[0098] S1, prepolymerization: place the mold in a constant temperature water bath at 35-50°C for 5 days to obtain a transparent PMI prepolymerized plate;

[0099] S2, heat treatment before foaming: put the PMI prepolymerized board into a circulating air oven at 100°C for 6 hours to obtain a PMI polymerized board;

[0100] S3, foaming: foaming the PMI polymer sheet at 200° C. for 4 hours to obtain PMI foam;

[0101] S4. Post-foaming heat treatment: The PMI foam is treated at 180° C. for 24 hours to obtain a high temperature resistant PMI foam.

[0102] Example 2

[0103] The foamable composition comprises 80 parts of methacrylonitrile as a first comonomer, 100 parts of methacrylic acid as a second comonomer, 2 parts of methacrylamide as a third comonomer, 2.5 parts of azobisisobutyronitrile as an initiator, 12.5 parts of formamide as a foaming agent, 2 parts of allyl methacrylate as a crosslinking agent, and 90 parts of polylactic acid as a degradation agent.

[0104] S0. Ingredients: Add 80 parts of methacrylonitrile, 100 parts of methacrylic acid, 2 parts of methacrylamide, 2.5 parts of azobisisobutyronitrile, 12.5 parts of formamide, and 2 parts of allyl methacrylate into a reaction kettle according to the weight parts, stir evenly, mix thoroughly at room temperature, and then pour into a mold;

[0105] S1, prepolymerization: place the mold in a constant temperature water bath at 35-50°C for 5 days to obtain a transparent PMI prepolymerized plate;

[0106] S2, heat treatment before foaming: put the PMI prepolymerized board into a circulating air oven at 100°C for 6 hours to obtain a PMI polymerized board;

[0107] S3, mixing: after the PMI polymer plate is crushed into particles, 90 parts of polylactic acid and 8 parts of epoxy resin are added, and the mixture is mixed and stirred evenly;

[0108] S4, foaming: placing the above PMI mixed material in a mold and foaming it at 200° C. for 4 hours to obtain PMI foam;

[0109] S5. Heat treatment after foaming: treating the PMI foam at 180° C. for 24 hours to obtain a high temperature resistant PMI foam.

[0110] Example 3

[0111] The foamable composition comprises 80 parts of methacrylonitrile as a first comonomer, 100 parts of methacrylic acid as a second comonomer, 2 parts of methacrylamide as a third comonomer, 2.5 parts of azobisisobutyronitrile as an initiator, 12.5 parts of formamide as a foaming agent, 2 parts of allyl methacrylate as a crosslinking agent, and 90 parts of polycaprolactone as a degradation agent.

[0112] S0. Ingredients: Add 80 parts of methacrylonitrile, 100 parts of methacrylic acid, 2 parts of methacrylamide, 2.5 parts of azobisisobutyronitrile, 12.5 parts of formamide, and 2 parts of allyl methacrylate into a reaction kettle according to the weight parts, stir evenly, mix thoroughly at room temperature, and then pour into a mold;

[0113] S1, prepolymerization: place the mold in a constant temperature water bath at 35-50°C for 5 days to obtain a transparent PMI prepolymerized plate;

[0114] S2, heat treatment before foaming: put the PMI prepolymerized board into a circulating air oven at 100°C for 6 hours to obtain a PMI polymerized board;

[0115] S3, mixing: after the PMI polymer plate is crushed into particles, 90 parts of polycaprolactone and 8 parts of epoxy resin are added, and the mixture is mixed and stirred evenly;

[0116] S4, foaming: placing the above PMI mixed material in a mold and foaming it at 200° C. for 4 hours to obtain PMI foam;

[0117] S5. Heat treatment after foaming: treating the PMI foam at 180° C. for 24 hours to obtain a high temperature resistant PMI foam.

[0118] Example 4

[0119] The foamable composition comprises 80 parts of methacrylonitrile as a first comonomer, 100 parts of methacrylic acid as a second comonomer, 2 parts of methacrylamide as a third comonomer, 2.5 parts of azobisisobutyronitrile as an initiator, 12.5 parts of formamide as a foaming agent, 2 parts of allyl methacrylate as a crosslinking agent, and 90 parts of starch-based polyether polyol as a degradation agent.

[0120] S0. Ingredients: Add 80 parts of methacrylonitrile, 100 parts of methacrylic acid, 2 parts of methacrylamide, 2.5 parts of azobisisobutyronitrile, 12.5 parts of formamide, and 2 parts of allyl methacrylate into a reaction kettle according to the weight parts, stir evenly, mix thoroughly at room temperature, and then pour into a mold;

[0121] S1, prepolymerization: place the mold in a constant temperature water bath at 35-50°C for 5 days to obtain a transparent PMI prepolymerized plate;

[0122] S2, heat treatment before foaming: put the PMI prepolymerized board into a circulating air oven at 100°C for 6 hours to obtain a PMI polymerized board;

[0123] S3, mixing: after the PMI polymer plate is crushed into particles, 90 parts of starch-based polyether polyol and 8 parts of epoxy resin are added, and the mixture is mixed and stirred evenly;

[0124] S4, foaming: placing the above PMI mixed material in a mold and foaming it at 200° C. for 4 hours to obtain PMI foam;

[0125] S5. Heat treatment after foaming: treating the PMI foam at 180° C. for 24 hours to obtain a high temperature resistant PMI foam.

[0126] Performance test 1

[0127] The PMI foam finally obtained in Example 1 to Example 4 was subjected to mechanical property tests such as PMI foam density, compression performance, tensile performance, and the measurement of the final biodegradation rate after 180 days. The density was tested according to GB / T 6343, the compression performance was tested according to GB / T 8813, the tensile performance was tested according to GB / T 1040.2, and the biodegradability was tested according to GB / T 19277.1-2011. The test results are as follows:

[0128] Test results table

[0129]

[0130] According to GB / T 20197-2006, when the biodegradation rate reaches 60% or more, it meets the technical requirements for the degradation performance of biodegradable plastics or compostable plastics. The test result table shows that after adding degradation agents polylactic acid, polycaprolactone, and starch-based polyether polyols to Examples 2 to 4, the biodegradation rate of PMI foam exceeded 60%, meeting the technical requirements for the degradation performance of biodegradable plastics or compostable plastics.

[0131] Generally speaking, the mechanical properties of PMI foams increase with increasing density. The foams of Examples 2 to 4 have higher densities than Example 1, but their mechanical properties are all lower than those of the foam of Example 1.

[0132] Example 5

[0133] The foamable composition comprises 80 parts of methacrylonitrile as a first comonomer, 100 parts of methacrylic acid as a second comonomer, 2 parts of methacrylamide as a third comonomer, 2.5 parts of azobisisobutyronitrile as an initiator, 12.5 parts of formamide as a foaming agent, 2 parts of allyl methacrylate as a crosslinking agent, and 90 parts of polylactic acid as a degradation agent.

[0134] S0. Ingredients: Add 80 parts of methacrylonitrile, 100 parts of methacrylic acid, 2 parts of methacrylamide, 2.5 parts of azobisisobutyronitrile, 12.5 parts of formamide, 2 parts of allyl methacrylate, and 90 parts of polylactic acid into a reaction kettle according to the weight parts, stir evenly, mix thoroughly at room temperature, and then pour into a mold;

[0135] S1. Prepolymerization: placing the mold in a constant temperature water bath at 35-50°C for 5 days to allow the degradation agent to polymerize with the MAA / MAN copolymer monomer in situ to obtain a polymethacrylimide (PMI) prepolymer containing a degradation agent block;

[0136] S2, heat treatment before foaming: put the PMI prepolymerized board into a circulating air oven at 100°C for 6 hours to obtain a PMI polymerized board;

[0137] S3, foaming: foaming the PMI polymer sheet at 200° C. for 4 hours to obtain PMI foam;

[0138] S4. Post-foaming heat treatment: The PMI foam is treated at 180° C. for 24 hours to obtain a high temperature resistant PMI foam.

[0139] Example 6

[0140] The foamable composition comprises 80 parts of methacrylonitrile as a first comonomer, 100 parts of methacrylic acid as a second comonomer, 2 parts of methacrylamide as a third comonomer, 2.5 parts of azobisisobutyronitrile as an initiator, 12.5 parts of formamide as a foaming agent, 2 parts of allyl methacrylate as a crosslinking agent, and 90 parts of polycaprolactone as a degradation agent.

[0141] S0. Ingredients: Add 80 parts of methacrylonitrile, 100 parts of methacrylic acid, 2 parts of methacrylamide, 2.5 parts of azobisisobutyronitrile, 12.5 parts of formamide, 2 parts of allyl methacrylate, and 90 parts of polycaprolactone into a reaction kettle according to the weight parts, stir evenly, mix thoroughly at room temperature, and pour into a mold;

[0142] S1. Polymerization: placing the mold in a constant temperature water bath at 35-50° C. for 5 days to allow the degradation agent and the MAA / MAN copolymer to be polymerized in situ to obtain a polymethacrylimide (PMI) prepolymer containing a degradation agent block;

[0143] S2, heat treatment before foaming: put the PMI prepolymerized board into a circulating air oven at 100°C for 6 hours to obtain a PMI polymerized board;

[0144] S3, foaming: foaming the PMI polymer sheet at 200° C. for 4 hours to obtain PMI foam;

[0145] S4. Post-foaming heat treatment: The PMI foam is treated at 180° C. for 24 hours to obtain a high temperature resistant PMI foam.

[0146] Example 7

[0147] The foamable composition comprises 80 parts of methacrylonitrile as a first comonomer, 100 parts of methacrylic acid as a second comonomer, 2 parts of methacrylamide as a third comonomer, 2.5 parts of azobisisobutyronitrile as an initiator, 12.5 parts of formamide as a foaming agent, 2 parts of allyl methacrylate as a crosslinking agent, and 90 parts of starch-based polyether polyol as a degradation agent.

[0148] S0. Ingredients: Add 80 parts of methacrylonitrile, 100 parts of methacrylic acid, 2 parts of methacrylamide, 2.5 parts of azobisisobutyronitrile, 12.5 parts of formamide, 2 parts of allyl methacrylate, and 90 parts of starch-based polyether polyol into a reaction kettle according to the weight parts, stir evenly, mix thoroughly at room temperature, and then pour into a mold;

[0149] S1. Prepolymerization: placing the mold in a constant temperature water bath at 35-50°C for 5 days to allow the degradation agent to polymerize with the MAA / MAN copolymer monomer in situ to obtain a polymethacrylimide (PMI) prepolymer containing a degradation agent block;

[0150] S2, heat treatment before foaming: put the PMI prepolymerized board into a circulating air oven at 100°C for 6 hours to obtain a PMI polymerized board;

[0151] S3, foaming: foaming the PMI polymer sheet at 200° C. for 4 hours to obtain PMI foam;

[0152] S4. Post-foaming heat treatment: The PMI foam is treated at 180° C. for 24 hours to obtain a high temperature resistant PMI foam.

[0153] Performance test 2

[0154] According to the method of performance test 1, the mechanical properties such as density, compression performance, tensile performance and the final biodegradation rate of the PMI foam obtained in Examples 5 to 7 were tested. The test results are as follows:

[0155] Test results table

[0156]

[0157] The test result table shows that after adding the degradation agents polylactic acid, polycaprolactone, and starch-based polyether polyol in Examples 5 to 7, the biodegradation rates of the PMI foams all exceeded 60%, meeting the technical requirements for the degradation performance of biodegradable plastics or compostable plastics.

[0158] Compared with the stepwise mixing and the addition of the degradation agent after the prepolymerization in Examples 2 to 4, the in-situ polymerization in Examples 5 to 7 added the degradation agent in the prepolymerization step. Examples 5 to 7 prepared PMI foams with a density basically the same as that of Example 1, and the mechanical properties were greatly improved compared with Examples 2 to 4. At the same time, the biodegradation rate of the PMI foams prepared in Examples 5 to 7 was also improved. In particular, in Example 5, the PMI foam prepared using polylactic acid as the degradation agent had a lower density than that of Examples 6 and 7, but the biodegradation rate and mechanical properties were better than those of Examples 6 and 7.

[0159] Example 8

[0160] The foamable composition comprises 80 parts of methacrylonitrile as a first comonomer, 100 parts of methacrylic acid as a second comonomer, 2 parts of methacrylamide as a third comonomer, 2.5 parts of azobisisobutyronitrile as an initiator, 12.5 parts of formamide as a foaming agent, 2 parts of allyl methacrylate as a crosslinking agent, and 30 parts of polylactic acid as a degradation agent.

[0161] S0. Ingredients: Add 80 parts of methacrylonitrile, 100 parts of methacrylic acid, 2 parts of methacrylamide, 2.5 parts of azobisisobutyronitrile, 12.5 parts of formamide, 2 parts of allyl methacrylate, and 30 parts of polylactic acid into a reaction kettle according to the weight parts, stir evenly, mix thoroughly at room temperature, and then pour into a mold;

[0162] S1. Prepolymerization: placing the mold in a constant temperature water bath at 35-50°C for 5 days to allow the degradation agent to polymerize with the MAA / MAN copolymer monomer in situ to obtain a polymethacrylimide (PMI) prepolymer containing a degradation agent block;

[0163] S2, heat treatment before foaming: put the PMI prepolymerized board into a circulating air oven at 100°C for 6 hours to obtain a PMI polymerized board;

[0164] S3, foaming: foaming the PMI polymer sheet at 200° C. for 4 hours to obtain PMI foam;

[0165] S4. Post-foaming heat treatment: The PMI foam is treated at 180° C. for 24 hours to obtain a high temperature resistant PMI foam.

[0166] Example 9

[0167] The foamable composition comprises 80 parts of methacrylonitrile as a first comonomer, 100 parts of methacrylic acid as a second comonomer, 2 parts of methacrylamide as a third comonomer, 2.5 parts of azobisisobutyronitrile as an initiator, 12.5 parts of formamide as a foaming agent, 2 parts of allyl methacrylate as a crosslinking agent, and 40 parts of polylactic acid as a degradation agent.

[0168] S0. Ingredients: Add 80 parts of methacrylonitrile, 100 parts of methacrylic acid, 2 parts of methacrylamide, 2.5 parts of azobisisobutyronitrile, 12.5 parts of formamide, 2 parts of allyl methacrylate, and 40 parts of polylactic acid into a reaction kettle according to the weight parts, stir evenly, mix thoroughly at room temperature, and then pour into a mold;

[0169] S1. Prepolymerization: placing the mold in a constant temperature water bath at 35-50°C for 5 days to allow the degradation agent to polymerize with the MAA / MAN copolymer monomer in situ to obtain a transparent polymethacrylimide (PMI) prepolymer containing a degradation agent block;

[0170] S2, heat treatment before foaming: put the PMI prepolymerized board into a circulating air oven at 100°C for 6 hours to obtain a PMI polymerized board;

[0171] S3, foaming: foaming the PMI polymer sheet at 200° C. for 4 hours to obtain PMI foam;

[0172] S4. Post-foaming heat treatment: The PMI foam is treated at 180° C. for 24 hours to obtain a high temperature resistant PMI foam.

[0173] Example 10

[0174] The foamable composition comprises 80 parts of methacrylonitrile as a first comonomer, 100 parts of methacrylic acid as a second comonomer, 2 parts of methacrylamide as a third comonomer, 2.5 parts of azobisisobutyronitrile as an initiator, 12.5 parts of formamide as a foaming agent, 2 parts of allyl methacrylate as a crosslinking agent, and 50 parts of polylactic acid as a degradation agent.

[0175] S0. Ingredients: Add 80 parts of methacrylonitrile, 100 parts of methacrylic acid, 2 parts of methacrylamide, 2.5 parts of azobisisobutyronitrile, 12.5 parts of formamide, 2 parts of allyl methacrylate, and 50 parts of polylactic acid into a reaction kettle according to the weight parts, stir evenly, mix thoroughly at room temperature, and then pour into a mold;

[0176] S1. Prepolymerization: placing the mold in a constant temperature water bath at 35-50°C for 5 days to allow the degradation agent to polymerize with the MAA / MAN copolymer monomer in situ to obtain a polymethacrylimide (PMI) prepolymer containing a degradation agent block;

[0177] S2, heat treatment before foaming: put the PMI prepolymerized board into a circulating air oven at 100°C for 6 hours to obtain a PMI polymerized board;

[0178] S3, foaming: foaming the PMI polymer sheet at 200° C. for 4 hours to obtain PMI foam;

[0179] S4. Post-foaming heat treatment: The PMI foam is treated at 180° C. for 24 hours to obtain a high temperature resistant PMI foam.

[0180] Embodiment 11

[0181] The foamable composition comprises 80 parts of methacrylonitrile as a first comonomer, 100 parts of methacrylic acid as a second comonomer, 2 parts of methacrylamide as a third comonomer, 2.5 parts of azobisisobutyronitrile as an initiator, 12.5 parts of formamide as a foaming agent, 2 parts of allyl methacrylate as a crosslinking agent, and 60 parts of polylactic acid as a degradation agent.

[0182] S0. Ingredients: Add 80 parts of methacrylonitrile, 100 parts of methacrylic acid, 2 parts of methacrylamide, 2.5 parts of azobisisobutyronitrile, 12.5 parts of formamide, 2 parts of allyl methacrylate, and 60 parts of polylactic acid into a reaction kettle according to the weight parts, stir evenly, mix thoroughly at room temperature, and then pour into a mold;

[0183] S1. Prepolymerization: placing the mold in a constant temperature water bath at 35-50°C for 5 days to allow the degradation agent to polymerize with the MAA / MAN copolymer monomer in situ to obtain a polymethacrylimide (PMI) prepolymer containing a degradation agent block;

[0184] S2, heat treatment before foaming: put the PMI prepolymerized board into a circulating air oven at 100°C for 6 hours to obtain a PMI polymerized board;

[0185] S3, foaming: foaming the PMI polymer sheet at 200° C. for 4 hours to obtain PMI foam;

[0186] S4. Post-foaming heat treatment: The PMI foam is treated at 180° C. for 24 hours to obtain a high temperature resistant PMI foam.

[0187] Example 12

[0188] The foamable composition comprises 80 parts of methacrylonitrile as a first comonomer, 100 parts of methacrylic acid as a second comonomer, 2 parts of methacrylamide as a third comonomer, 2.5 parts of azobisisobutyronitrile as an initiator, 12.5 parts of formamide as a foaming agent, 2 parts of allyl methacrylate as a crosslinking agent, and 70 parts of polylactic acid as a degradation agent.

[0189] S0. Ingredients: Add 80 parts of methacrylonitrile, 100 parts of methacrylic acid, 2 parts of methacrylamide, 2.5 parts of azobisisobutyronitrile, 12.5 parts of formamide, 2 parts of allyl methacrylate, and 70 parts of polylactic acid into a reaction kettle according to the weight parts, stir evenly, mix thoroughly at room temperature, and then pour into a mold;

[0190] S1. Prepolymerization: placing the mold in a constant temperature water bath at 35-50°C for 5 days to allow the degradation agent to polymerize with the MAA / MAN copolymer monomer in situ to obtain a polymethacrylimide (PMI) prepolymer containing a degradation agent block;

[0191] S2, heat treatment before foaming: put the PMI prepolymerized board into a circulating air oven at 100°C for 6 hours to obtain a PMI polymerized board;

[0192] S3, foaming: foaming the PMI polymer sheet at 200° C. for 4 hours to obtain PMI foam;

[0193] S4. Post-foaming heat treatment: The PMI foam is treated at 180° C. for 24 hours to obtain a high temperature resistant PMI foam.

[0194] Embodiment 13

[0195] The foamable composition comprises 80 parts of methacrylonitrile as a first comonomer, 100 parts of methacrylic acid as a second comonomer, 2 parts of methacrylamide as a third comonomer, 2.5 parts of azobisisobutyronitrile as an initiator, 12.5 parts of formamide as a foaming agent, 2 parts of allyl methacrylate as a crosslinking agent, and 80 parts of polylactic acid as a degradation agent.

[0196] S0. Ingredients: Add 80 parts of methacrylonitrile, 100 parts of methacrylic acid, 2 parts of methacrylamide, 2.5 parts of azobisisobutyronitrile, 12.5 parts of formamide, 2 parts of allyl methacrylate, and 80 parts of polylactic acid into a reaction kettle according to the weight parts, stir evenly, mix thoroughly at room temperature, and then pour into a mold;

[0197] S1. Prepolymerization: placing the mold in a constant temperature water bath at 35-50°C for 5 days to allow the degradation agent to polymerize with the MAA / MAN copolymer monomer in situ to obtain a polymethacrylimide (PMI) prepolymer containing a degradation agent block;

[0198] S2, heat treatment before foaming: put the PMI prepolymerized board into a circulating air oven at 100°C for 6 hours to obtain a PMI polymerized board;

[0199] S3, foaming: foaming the PMI polymer sheet at 200° C. for 4 hours to obtain PMI foam;

[0200] S4. Post-foaming heat treatment: The PMI foam is treated at 180° C. for 24 hours to obtain a high temperature resistant PMI foam.

[0201] Embodiment 14

[0202] The foamable composition comprises 80 parts of methacrylonitrile as a first comonomer, 100 parts of methacrylic acid as a second comonomer, 2 parts of methacrylamide as a third comonomer, 2.5 parts of azobisisobutyronitrile as an initiator, 12.5 parts of formamide as a foaming agent, 2 parts of allyl methacrylate as a crosslinking agent, and 100 parts of polylactic acid as a degradation agent.

[0203] S0. Ingredients: Add 80 parts of methacrylonitrile, 100 parts of methacrylic acid, 2 parts of methacrylamide, 2.5 parts of azobisisobutyronitrile, 12.5 parts of formamide, 2 parts of allyl methacrylate, and 100 parts of polylactic acid into a reaction kettle according to the weight parts, stir evenly, mix thoroughly at room temperature, and then pour into a mold;

[0204] S1. Prepolymerization: placing the mold in a constant temperature water bath at 35-50°C for 5 days to allow the degradation agent to polymerize with the MAA / MAN copolymer monomer in situ to obtain a polymethacrylimide (PMI) prepolymer containing a degradation agent block;

[0205] S2, pre-foaming treatment: put the PMI pre-polymerized board into a circulating air oven at 100°C for 6 hours to obtain a PMI polymerized board;

[0206] S3, foaming: foaming the PMI polymer sheet at 200° C. for 4 hours to obtain PMI foam;

[0207] S4. Post-foaming heat treatment: The PMI foam is treated at 180° C. for 24 hours to obtain a high temperature resistant PMI foam.

[0208] Embodiment 15

[0209] The foamable composition comprises 80 parts of methacrylonitrile as a first comonomer, 100 parts of methacrylic acid as a second comonomer, 2 parts of methacrylamide as a third comonomer, 2.5 parts of azobisisobutyronitrile as an initiator, 12.5 parts of formamide as a foaming agent, 2 parts of allyl methacrylate as a crosslinking agent, and 110 parts of polylactic acid as a degradation agent.

[0210] S0. Ingredients: Add 80 parts of methacrylonitrile, 100 parts of methacrylic acid, 2 parts of methacrylamide, 2.5 parts of azobisisobutyronitrile, 12.5 parts of formamide, 2 parts of allyl methacrylate, and 110 parts of polylactic acid into a reaction kettle according to the weight parts, stir evenly, mix thoroughly at room temperature, and then pour into a mold;

[0211] S1. Prepolymerization: placing the mold in a constant temperature water bath at 35-50°C for 5 days to allow the degradation agent to polymerize with the MAA / MAN copolymer monomer in situ to obtain a polymethacrylimide (PMI) prepolymer containing a degradation agent block;

[0212] S2, pre-foaming treatment: put the PMI pre-polymerized board into a circulating air oven at 100°C for 6 hours to obtain a PMI polymerized board;

[0213] S3, foaming: foaming the PMI polymer sheet at 200° C. for 4 hours to obtain PMI foam;

[0214] S4. Post-foaming heat treatment: The PMI foam is treated at 180° C. for 24 hours to obtain a high temperature resistant PMI foam.

[0215] Performance test 3

[0216] According to the method of performance test 1, the mechanical properties such as density, compression performance, tensile performance and the final biodegradation rate of the PMI foam obtained in Examples 8 to 11 were tested. The test results are as follows:

[0217] Test results table

[0218]

[0219] The test result table shows that after adding 30-110 parts of the degradation agent polylactic acid in Examples 8 to 15, the biodegradation rate of the PMI foam exceeded 60%, meeting the technical requirements for the degradation performance of biodegradable plastics or compostable plastics.

[0220] Compared with Example 5 in which 90 parts of polylactic acid were added, the mechanical properties of Examples 14 and 15 in which more than 100 parts of polylactic acid were added were significantly reduced.

[0221] Example 16

[0222] The foamable composition comprises 100 parts of acrylonitrile as a first comonomer, 80 parts of methacrylic acid as a second comonomer, 1 part of acrylamide as a third comonomer, 2 parts of tert-butyl peroxy(2-ethylhexanoate) as an initiator, 15 parts of isopropyl alcohol as a foaming agent, and 1 part of magnesium methacrylate as a crosslinking agent.

[0223] S0. Ingredients: Add 100 parts of acrylonitrile, 80 parts of methacrylic acid, 1 part of acrylamide, 2 parts of tert-butyl peroxide (2-ethylhexanoate), 15 parts of isopropanol, and 1 part of magnesium methacrylate into a reaction kettle according to the weight parts, stir evenly, mix thoroughly at room temperature, and then pour into a mold;

[0224] S1, prepolymerization: place the mold in a constant temperature water bath at 35-50°C for 5 days to obtain a transparent PMI prepolymerized plate;

[0225] S2, heat treatment before foaming: put the PMI prepolymerized board into a circulating air oven at 100°C for 6 hours to obtain a PMI polymerized board;

[0226] S3, foaming: foaming the PMI polymer sheet at 200° C. for 4 hours to obtain PMI foam;

[0227] S4. Post-foaming heat treatment: The PMI foam is treated at 180° C. for 24 hours to obtain a high temperature resistant PMI foam.

[0228] Embodiment 17

[0229] The foamable composition comprises 100 parts of acrylonitrile as a first comonomer, 80 parts of methacrylic acid as a second comonomer, 1 part of acrylamide as a third comonomer, 2 parts of tert-butyl peroxide (2-ethylhexanoate) as an initiator, 15 parts of isopropyl alcohol as a foaming agent, 1 part of magnesium methacrylate as a crosslinking agent, and 90 parts of polylactic acid as a degradation agent.

[0230] S0. Ingredients: Add 100 parts of acrylonitrile, 80 parts of methacrylic acid, 1 part of acrylamide, 2 parts of tert-butyl peroxide (2-ethylhexanoate), 15 parts of isopropanol, 1 part of magnesium methacrylate, and 90 parts of polylactic acid into a reaction kettle according to the weight parts, stir evenly, mix thoroughly at room temperature, and then pour into a mold;

[0231] S1. Prepolymerization: placing the mold in a constant temperature water bath at 35-50° C. for 5 days to allow the degradation agent and the MAA / AN comonomer to be polymerized in situ to obtain a polymethacrylimide (PMI) prepolymer containing a degradation agent block;

[0232] S2, heat treatment before foaming: put the PMI prepolymerized board into a circulating air oven at 100°C for 6 hours to obtain a PMI polymerized board;

[0233] S3, foaming: foaming the PMI polymer sheet at 200° C. for 4 hours to obtain PMI foam;

[0234] S4. Post-foaming heat treatment: The PMI foam is treated at 180° C. for 24 hours to obtain a high temperature resistant PMI foam.

[0235] Performance test 4

[0236] According to the method of performance test 1, the mechanical properties such as density, compression performance, tensile performance and the final biodegradation rate of the PMI foam obtained in Examples 16 and 17 were tested. The test results are as follows:

[0237] Test results table

[0238]

[0239]

[0240] The test result table shows that after adding the degradation agent polylactic acid to the basic formula 2 of the present disclosure, the biodegradation rate of the PMI foam exceeds 60%, reaching the technical requirements for the degradation performance of biodegradable plastics or compostable plastics.

[0241] Compared with Example 5, Example 17 has a different basic formula, but the same degradation agent is added, and the final PMI foam tensile modulus is significantly improved.

[0242] In summary, the biodegradable PMI foam and preparation method thereof provided in the embodiments of the present disclosure improve the biodegradation rate of the PMI foam by scientifically adding degradation agents and adjusting the formula. The technical solutions provided in some embodiments of the present disclosure also retain the high mechanical properties of the PMI foam.

[0243] Although embodiments of the present disclosure have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present disclosure, and the scope of the present disclosure is defined by the equivalents of the appended claims.

Claims

1. A foamable composition comprising a comonomer, an initiator, a blowing agent and a crosslinking agent, wherein the comonomer comprises a first comonomer and a second comonomer, characterized in that: The first comonomer is selected from one or both of methacrylonitrile and acrylonitrile, and the second comonomer is selected from methacrylic acid; The composition further comprises a degradation agent, wherein the degradation agent is selected from one or a combination of two or more of polylactic acid, starch-based polyether polyol, and polycaprolactone; The mass ratio of the degradation agent to the comonomer is 30-132:

180.

2. The foamable composition according to claim 1, wherein The comonomer further comprises a third comonomer, and the third comonomer is selected from acrylamide monomers.

3. The foamable composition according to claim 2, wherein The acrylamide monomer is selected from any one of acrylamide, methacrylamide, N-hydroxymethyl acrylamide, and N,N-dimethyl acrylamide, or a combination of two or more thereof.

4. The foamable composition according to any one of claims 1 to 3, wherein The initiator is selected from azobisisobutyronitrile, Any one of azobisisoheptanenitrile, tert-butyl peroxide (2-ethylhexanoate) and dilauroyl peroxide, or a combination of two or more thereof; the foaming agent is selected from any one of formamide, N,N-dimethylformamide, isopropanol, isobutanol, octane and isooctane, or a combination of two or more thereof; the cross-linking agent is any one of allyl methacrylate and magnesium methacrylate, or two or more thereof.

5. The foamable composition according to any one of claims 1 to 4, wherein: The molecular weight of the polylactic acid is 30,000-150,000, the molecular weight of the polycaprolactone is 10,000-120,000, and the hydroxyl value of the starch-based polyether polyol is 300-600 mgKOH / g.

6. The foamable composition according to any one of claims 1 to 5, wherein: The degradation agent is selected from polylactic acid.

7. The foamable composition according to any one of claims 1 to 6, wherein: The mass ratio of the degradation agent to the comonomer is 50-110:

180.

8. The foamable composition according to any one of claims 1 to 7, wherein: The mass ratio of the first comonomer to the second comonomer is 0.6-1.5:

1.

9. The foamable composition according to any one of claims 1 to 8, wherein: By mass, it includes 64-120 parts of the first comonomer, 64-120 parts of the second comonomer, 1.2-3 parts of the initiator, 10-18 parts of the foaming agent, 0.8-2.4 parts of the crosslinking agent, The degradation agent is 30-132 parts, and the third comonomer is 0-2.4 parts.

10. The foamable composition according to claim 9, wherein By mass, it includes 72-110 parts of the first comonomer, 72-110 parts of the second comonomer, 1.8-2.75 parts of the initiator, 11.25-16.5 parts of the foaming agent, 0.9-2.2 parts of the crosslinking agent, 40-121 parts of degradation agent and 0.9-2.2 parts of the third comonomer.

11. The foamable composition according to claim 1, wherein By mass, it includes 72-88 parts of the first comonomer methacrylonitrile, 90-110 parts of the second comonomer methacrylic acid, 1.8-2.2 parts of the third comonomer methacrylamide, 2-2.75 parts of the initiator azobisisobutyronitrile, 11.25-13.75 parts of the foaming agent formamide, 1.8-2.2 parts of the crosslinking agent allyl methacrylate, and 30-99 parts of the degradation agent polylactic acid.

12. The foamable composition according to claim 1, wherein By mass, it includes 90-110 parts of acrylonitrile as the first comonomer, 72-88 parts of methacrylic acid as the second comonomer, 0.9-1.1 parts of acrylamide as the third comonomer, 1.8-2.2 parts of tert-butyl peroxide (2-ethylhexanoate) as the initiator, 13.5-16.5 parts of isopropyl alcohol as the foaming agent, 0.9-1.1 parts of magnesium methacrylate as the crosslinking agent, and 30-99 parts of polylactic acid as the degradation agent.

13. The foamable composition according to any one of claims 9 to 12, wherein: Calculated by mass, the composition comprises 70-90 parts of a degradation agent.

14. A biodegradable foam, characterized in that: The method is obtained by foaming the foamable composition according to any one of claims 1 to 13.

15. A method for preparing biodegradable foam, characterized in that: The following steps are involved: S1. Prepolymerization: subjecting the foamable composition according to any one of claims 1 to 13 to polymerization to obtain a prepolymer; S2, heat treatment before foaming: heat treating the prepolymer to obtain a polymer; S3, foaming: foaming the polymer to obtain foam.

16. The preparation method according to claim 15, wherein: In step S1, the polymerization reaction system contains a degradation agent, a comonomer, an initiator, a foaming agent and a cross-linking agent.

17. The preparation method according to claim 15 or 16, wherein: In step S1, the polymerization reaction temperature is 20°C-60°C.

18. The preparation method according to any one of claims 15 to 17, wherein: The heat treatment temperature in step S2 is 60°C-120°C.

19. The preparation method according to any one of claims 15 to 18, wherein: The foaming temperature in step S3 is 160°C-250°C.

20. The preparation method according to any one of claims 15 to 19, further comprising the following steps: S4. Heat treatment after foaming: heat treating the foam at 135° C.-220° C. to obtain high temperature resistant foam.

Citation Information

Patent Citations

  • A biodegradable PBAT-based foam material and its preparation method

    CN108264736B

  • A biodegradable polypropylene plastic, its preparation method and application

    CN112063042B

  • Methods relating to polyurethane foam-containing and degradable foam-containing tires, and degradable foam-containing tires

    US11597235B2

  • Biodegradable plastic and manufacture thereof from recyclable plastic

    US9914824B2

Cited By

  • Foamable composition, biodegradable PMI foam, and preparation method therefor

    EP4790093A1

  • Foamable composition, biodegradable PMI foam, and preparation method therefor

    WO2026108112A1